การศึกษาประสิทธิภาพของการใช้ ออดิโอ-อาร็่ทิคิวเลชันโมเดล เพื่อพัฒนาการออกเสียงเสียดแทรกในกลุ่มนักศึกษาไทย - อิ่มเอมทรัพย์, อัมพวรรณ; กุลสิริสวัสดิ, พณิตา; จันทร์เสม, อัญชลี (Community and Social Development Journal, 2012)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาประสิทธิภาพของการใช้ Audioarticulation Model ในการพัฒนาการออกเสียงเสียดแทรกในกลุ่มนักศึกษาไทยและเจตคติที่ได้รับจากการสอนด้วยวิธีดังกล่าว นักศึกษากลุ่มทดลองคือ นักศึกษาชั้นปีที่สาม คณะครุศาสตร์ มหาวิทยาลัยราชภัฏเชียงใหม่สาขาวิชาภาษาอังกฤษ จำนวน 8 คน ในการแกอบรมโดยใช้เทคนิค AAM เป็นระยะเวลา 12 สัปดาห์งานวิจัยในครั้งนี้เป็นการศึกษาแบบการวิจัยกึ่งทดลอง ซึ่งประกอบด้วยการวิเคราะห์เชิงปริมาณและการวิเคราะห์เชิงคุณภาพ กลุ่มตัวอย่างทำการทดสอบก่อนและหลังเรียน ตลอดระยะเวลาในการฝึกอบรมกลุ่มตัวอย่างต้องเขียนสรุปความรู้หลังการเรียน และในชั่วโมงสุดท้ายของการเรียนกลุ่มตัวอย่างทำแบบสอบถามวัดระดับเจตคติต่อการเรียนการสอน Mann-Whitney บ Test ได้รับการปรับใช้เพื่อการวิเคราะห์พัฒนาการด้านการออกเสียง ระบบ รหัสปลายเปิดได้รับการนำมาใช้เพื่อวิเคราะห์แบบสอบถาม นอกจากนี้กลุ่มตัวอย่างจำนวนสามคนได้รับการสุ่มเลือกเป็นกลุ่ม nested cases ในการวิเคราะห์ปฏิกิริยาของกลุ่มตัวอย่างต่อการเรียนด้วยเทคนิค AAM และ เพื่อสนับสนุนผลการวิจัย ผลการวิจัยพบว่า กลุ่มตัวอย่างมีพัฒนาการด้านการออกเสียงที่ดีขึนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 อีกทั้งมีเจตคติที่ดีต่อการใช้ AAM และผลการศึกษาในกลุ่ม nested caseจำนวนสามคนพบว่า ระยะเวลาและเทคนิคที่ใช้ในการแกอบรมสามารถช่วยให้กลุ่มตัวอย่างมีพัฒนาการด้านการออกเสียงเสียดแทรกที่ดีขึน A Study of the Efectiveness of an Audioarticulation Model in Improving Thai Learners’ Pronunciation of Fricative Sounds The objectives of this research were to investigate the effectiveness of the Audioarticulation model (AAM) in improving the pronunciation of English fricative sounds among adult Thai stadents and their attitude toward the AAM. Eight third year English Education students from Chiangmai Rajabhat University participated in the pronunciation training course based on AAM for 12 weeks. The study was quasi-experimental design with both quantitative and qualitative data analyses. The participants took pronunciation tests before and after the training course. During the course, they completed the learning logs and a questionnaire developed for measuring their attitudes toward the course. The Mann-Whiney บ Test was applied to detect whether the participants have made any improvement in pronouncing English fricative sounds. The open coding system was used as a guideline for the analysis of the questionnaire. The three participants were purposive selected to be nested cases and individually analyze how the student engage with AAM and support three research questions. The findings indicated that all participants significantly improved their pronunciation of fricative sounds at the .05 level. They had positive attitudes toward the AAM. The three nested cases revealed that class hour and teaching techniques using in the training course helped them improve their pronunciation of fricative sounds.